Phytotoxic Activity of Parthenium Against Wheat and Canola Differ With Plant Parts and Bioassays Techniques - KHALIQ,A. (2016)
Phytotoxic effects of invasive weed Parthenium hysterophorus were studied by using whole plant, leaf and root aqueous extracts at 0, 2.5, 5.0, 7.5 and 10% (w/v) concentrations against germination and early seedling growth of wheat and canola. Studies were carried out both in Petri plates with filter paper as substratum placed in controlled conditions and soil-filled plastic pots placed in open environments. Pronounced variation was noted for phytotoxic activity of different plant parts of parthenium, aqueous extract concentrations, test species, and bioassay techniques. Aqueous parthenium extracts either inhibited or delayed the germination and suppressed seedling growth of test species over control. For both test species, all the germination attributes were suppressed to a greater extent in Petri plates than in plastic pots. Leaf extracts were more suppressive to germination of test species than whole plant and root extracts. Increasing extract concentration beyond 2.5% caused significant reduction in seedling dry biomass of both test species. Aqueous parthenium extract diminished chlorophyll contents of wheat and canola by 32-63% and 29 69%, respectively. Nevertheless, an increase of 9-172% and 22-60% in phenolic contents of wheat and canola was recorded. Canola appeared to be more susceptible than wheat at all extract concentrations. Present study concluded that bioassays conducted under controlled condition using filter paper as substratum may be misleading due to over estimation of allelopathic response and variation in potential of receiver and donor species. Furthermore, it implies that threshold concentrations of allelochemicals for test species in Petri plates are rarely reached under field conditions.